On the Viscoelastic Drift Behavior During Nanoindentation - Shen, Yu-Lin (Frontiers in Materials, 2022)
Nanoindentation measurements frequently involve a hold period at the peak load to allow the material to reach a stabilized state. A dwell time is also commonly employed at a sufficiently low load after unloading, to quantify the thermal drift for correction of the raw load-displacement data. This communication presents numerical case studies of indentation loading on a viscoelastic thin film using the finite element method. We illustrate that a simple viscoelastic material can actually induce prominent drift even under a low indentation load. The drift is caused by the material itself, unrelated to the thermal drift of the instrument. The direction and magnitude of the viscoelastic drift are controlled by the prior loading/unloading history as well as the load-displacement response of the fully relaxed elastic state.